The Babylon Complex : Theopolitical Fantasies of War, Sex, and Sovereignty. - Runions, Erin (Fordham University Press, 2014)
Babylon is a surprisingly multivalent symbol in U.S. culture and politics. Political citations of Babylon range widely, from torture at Abu Ghraib to depictions of Hollywood glamour and decadence. In political discourse, Babylon appears in conservative ruminations on democratic law, liberal appeals to unity, Tea Party warnings about equality, and religious advocacy for family values. A composite biblical figure, Babylon is used to celebrate diversity and also to condemn it, to sell sexuality and to regulate it, to galvanize war and to worry about imperialism. Erin Runions explores the signific.